An overview of the psychological complexities in sports performance - Galily, Y.; Samuel, R. D.; Tenenbaum, G. (Asian Journal of Sport and Exercise Psychology, 2024)
Our special issue comprises a diverse collection of ten research and review articles, each offering unique insights into the psychological dimensions of athletic performance. From studies examining the role of resilience in overcoming extreme score shifts to explorations of the mental toll caused by external crises like the COVID-19 pandemic and geopolitical conflict, these papers provide a broad spectrum of perspectives. The issue digs into critical topics such as the influence of crowd dynamics, athlete-coach relationships, and the psychological challenges of breaking long-standing records, all while highlighting innovative methodologies like ecological approaches and creative non-fiction. Together, these ten papers underscore the complexity of the psychological factors that impact athletes` success and well-being, offering both theoretical advances and practical applications for the sporting world.